Behinderung und Menschenrechte: Ein Verhältnis auf dem Prüfstand - Wohlgensinger, Corinne (Verlag Barbara Budrich, 2014)
The author addresses two groundbreaking questions: What significance does the Convention on the Rights of Persons with Disabilities have for special educational thinking and action? And how important is disability in the human rights debate? By describing the specific risk situations of people with disabilities, the author creates the basis for a reflection on the claims of justification and validity on the part of philosophy and points of departure for the special educational discussion.